2022
DOI: 10.2147/jir.s387809
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Nomogram for Identifying Refractory Mycoplasma pneumoniae Pneumonia Among Macrolide-Unresponsive Mycoplasma pneumoniae Pneumonia in Children

Abstract: Objective The individualized prediction of treatment regimens of macrolide-unresponsive Mycoplasma pneumoniae pneumonia (MUMPP) is scarce. The aim of this study was, therefore, to evaluate the relevant data of patients and construct a nomogram for identifying refractory Mycoplasma pneumoniae pneumonia (RMPP) among children continued to be treated with macrolide after the confirmation of MUMPP, providing a reference for the choice of treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…When the cell dissolves or the cell membrane is damaged, LDH is released into the blood, so it can be used as a biomarker of tissue injury. 20 A number of previous studies 17,18,[21][22][23] have suggested the important predictive value of LDH in the poor prognosis of MPP. In our prediction model, CRP and LDH were also selected as predictors, suggesting that the immune response plays an important role in the pathogenesis of NP.…”
Section: Discussionmentioning
confidence: 99%
“…When the cell dissolves or the cell membrane is damaged, LDH is released into the blood, so it can be used as a biomarker of tissue injury. 20 A number of previous studies 17,18,[21][22][23] have suggested the important predictive value of LDH in the poor prognosis of MPP. In our prediction model, CRP and LDH were also selected as predictors, suggesting that the immune response plays an important role in the pathogenesis of NP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LDH is also often used as a predictor of severe pneumonia. 18 , 19 A retrospective analysis of NP by Li et al 11 found that CRP is an independent predictor of the degree of lung necrosis. CRP > 48.35 mg/L had a high predictive value for the diagnosis of NP, according to Qian et al 7 Zhou et al 20 found that WBC and CRP in the NP group caused by Mycoplasma pneumoniae were significantly higher than those in non-NP group.…”
Section: Discussionmentioning
confidence: 99%
“…16 Macrolide-unresponsive Mycoplasma pneumoniae pneumonia (MUMPP) is defined as persistent fever ≥3 days after macrolide treatment. 17 RMPP is defined as clinical and radiological deterioration despite appropriate antibiotic therapy for at least seven days. 8 Treatment failure was defined as the progression to RMPP in children with MUMPP with the A/2063/2064G mutation.…”
Section: Methodsmentioning
confidence: 99%